Pengaruh Gaya Kepemimpinan Dan Komunikasi Terhadap Kinerja Pegawai Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kabupaten Karawang - Deni Sobari; Sonny Hersona; Nunung Nurhasanah (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Creating good governance conditions is a dream for every Organsiasi Perangkat Daerah (OPD), including the Dinas Pekerjaan Umum dan Penataan Ruang, Karawang Regency. However, to achieve this requires the support of qualified human resources in order to be able to produce better organizational performance. Organizational performance can be achieved with the condition that high employee performance is the main driver in regional apparatus organizations or other organizations. The increase in employee performance is thought to be influenced by leadership and communication styles. Thus, the purpose of this study was to determine and explain whether leadership and communication styles partially and simultaneously influence employee performance. The population used is all employees of Dinas Pekerjaan Umum dan Penataan Ruang in Karawang Regency, with a sample of 100 people. The analytical tool used is multiple linear regression analysis. The results of the partial and simultaneous analysis show that leadership and communication styles have an effect on increasing employee performance at Dinas Pekerjaan Umum dan Penataan Ruang, Karawang Regency. Keywords: leadership style, communication, employee performance